A numerical study of sedimentation of rod like particles using smooth profile method. (June 2020) - Hamid, A.; Arshad, A.B.; Mehdi, S.; Qasim, M.D.; Ullah, A.; Molina, J.J.; Yamamoto, R.
Highlights: This work is the first ever attempt to use the Smooth Profile method for the rod-like particles. The scaling of velocity fluctuations and their relaxation times and the orientation preference of the particles with respect to volume fraction is explored. Normalized drag and lift coefficients of a single rod of aspect ratio 3, followed the well known sin 2 θ and sinθcosθ curves, against the incident angle θ, respectively. We found that the inhomogeneity in the microstructure of the settling rods cause the formation of clusters, even at low volume fractions. These clusters move as a large lump, inducing pronounced hydrodynamic interactions. The average settling velocity normalized by the terminal velocity of an isolated rod, shows a non-monotonic behavior; increasing at low concentration because of these pronounced hydrodynamic interactions. Histogram of particles' orientation angle shows that the majority of the particles are vertically aligned. Abstract: Hydrodynamics of rod-like particles, found extensively in the chemical and process industry, is investigated here, using direct numerical simulations. A recently developed formulation of the smoothed profile method for rigid bodies is first validated for rod-like particles (rods) and then used to characterize the concentration effects on the static and dynamic properties of rods in the Stokes regime. Normalized drag and lift coefficients of a single rod of aspect ratio 3 and 4, followed the well known sin 2 θ and sin θ cos θ curves against the incident angle ( θ ), respectively. We found significant inhomogeneity in the microstructure of the settling rods. These inhomogeneties, cause the formation of clusters, even at low volume fractions. These clusters move as a large lump, inducing pronounced hydrodynamic interactions, which have significant effects on the settling system. The average settling velocity normalized by the terminal velocity of an isolated rod, shows a non-monotonic behavior; increasing at low concentration because of the cluster formation in which rod packets settle faster than an isolated rod, and decreasing at high concentration because of many particle interactions. Furthermore, velocity fluctuations are larger than those of spherical particles because of the cluster formation. Histogram of particles' orientation angle shows that the majority of the particles are vertically aligned.